2017
DOI: 10.1002/jnr.24122
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp stem cells and the management of neurological diseases: An update

Abstract: Medical research in regenerative medicine has brought promising perspectives for the use of stem cells in clinical trials. Stem cells are undifferentiated cells capable of multilineage differentiation and available in numerous sources in the human body. Dental pulp constitutes an attractive source of these cells since collecting mesenchymal stem cells from this site is a noninvasive practice that can be performed after a common surgical extraction of supernumerary or wisdom teeth. Thus, tissue sacrifice is ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…HDPSCs, which are successfully isolated from human third molars in 2000 for the first time, are increasingly being recognized as a viable cell source for dental regenerative medicine [11, 12]. Research on hDPSCs has become one of the fastest-growing areas in regenerative medicine, mainly because hDPSCs have the following characteristics: they are easy accessible, they share the same origin, the efficiency and success rate of isolating are high, the lifespan of these stem cells is long, and these cells can be safely cryopreserved [1316]. HDPSCs share similar features with undifferentiated mesenchymal stem cells, which own remarkable self-renewal potential and multilineage differentiation capability [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…HDPSCs, which are successfully isolated from human third molars in 2000 for the first time, are increasingly being recognized as a viable cell source for dental regenerative medicine [11, 12]. Research on hDPSCs has become one of the fastest-growing areas in regenerative medicine, mainly because hDPSCs have the following characteristics: they are easy accessible, they share the same origin, the efficiency and success rate of isolating are high, the lifespan of these stem cells is long, and these cells can be safely cryopreserved [1316]. HDPSCs share similar features with undifferentiated mesenchymal stem cells, which own remarkable self-renewal potential and multilineage differentiation capability [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Other eminent sources of adult MSCs include placenta, umbilical cord, amniotic fluid, adipose tissue, dental pulp, breast milk, and synovium [ 10 ]. The oral cavity as well as the extracted teeth constitute a remarkable source since they produce a variety of somatic stem cells [ 11 ]. The major differences in the stem cells arising from different sources are exhibited in their immunophenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dental pulp can be easily isolated from the surgical waste derived from deciduous tooth or wisdom tooth extraction [ 15 ]. The very low morbidity of the anatomical site after the collection of the pulp, the high efficiency of the extraction procedure of stem cells from the pulp tissue, the differentiation ability, and the demonstrated interactivity of stem cells derived from dental pulp with biomaterials for tissue engineering applications hold to DPSCs a great potential for clinical purposes [ 11 , 16 ]. Although it has been well demonstrated that MSCs from various sources are able to sustain bone regeneration [ 17 ], only recent tissue engineering approaches have shown that DPSCs constitute a valuable cell source for the healing of bone tissue when supported by a suitable scaffold [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The science of stem cells and their clinical use in regenerative medicine and dentistry have developed significantly over the past decade. 1 , 2 Stem cells have the potential to repair damaged teeth, tissue regeneration of dentin, and periodontal ligament, inducing bone regeneration and treating neural injury. 3 Teeth can provide a good source of stem cells that can grow rapidly.…”
Section: Introductionmentioning
confidence: 99%